-Omics studies of plant biology in spaceflight: A critical review of recent experiments - Hughes, Ariel M.; Kiss, John Z. (Frontiers in Astronomy and Space Sciences, 2022)
Researchers have been studying transcriptomic and proteomic responses of plants to ranges of reduced gravitational conditions. These include blue and red light in microgravity, circadian rhythms in microgravity, microgravity in different ecotypes, microgravity on suborbital flights, and they have using a variety of experimental equipment. Recent findings have linked microgravity and transcriptomic changes in genes relating to cell wall synthesis and modification, oxidative stress, abiotic stressors, phytohormones, sugar synthesis and metabolism, ribosomal biogenesis, and plant defense to other organisms. Although we have a better-established profile of the transcriptomic response of plants to reduced gravity, some areas of study have not yet been thoroughly investigated. The initial stages and progression of transcriptional responses to microgravity, the responses of additional plant species, and tissue-specific transcriptional responses to microgravity should all be further investigated in order to better develop our understanding of how plants react to a reduced gravity environment. In the near future, advancing technology, rapidly growing databases, and an increasing number of spaceflight opportunities will allow for more research to be conducted to address these and many other related questions in plant space biology.